Socio-cognitive processing in people with eating disorders: computerized tests of mentalizing, empathy and imitation skills - Corsi, E; Cardi, V; Sowden, S; Coll, M-P; Cascino, G; Ricca, V; Treasure, J; Bird, GP; Monteleone, AM (Wiley, 2021)
Objective Eating disorders are psychiatric illnesses characterized by extreme eating behaviors, such as sustained food restriction or loss of control over eating. Symptoms are thought to be maintained by a variety of mechanisms, one of which may be the socio-cognitive impairments associated with eating disorders. While some previous work has addressed socio-cognitive impairments in eating disorders, this work has relied mostly on self-report data.